Molecular Marker Technology for Crop Improvement (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Since the 1980s, agriculture and plant breeding have changed with the development of molecular marker technology. In recent decades, different types of molecular markers have been used for different purposes: mapping, marker-assisted selection, characterization of genetic resources, etc. These have produced effective genotyping, but the results have been costly and time-consuming due to the small number of markers that could be tested simultaneously. Recent advances in molecular marker technologies such as the development of high-throughput genotyping platforms, genotyping by sequencing, and the release of the genome sequences of major crop plants have opened new possibilities for advancing crop improvement. This Special Issue collects 16 research studies, including the application of molecular markers in 11 crop species, from the generation of linkage maps and diversity studies to the application of marker-assisted selection and genomic prediction.